Factors Correlated with Unavoidable 72-h Emergency Department Return Visits: A Retrospective Cohort Study - R Ajay Christopher; Darpanarayan Hazra; Aparna Lohanathan; Ankita Chowdary Nekkanti; Rathijit Pal; Kundavaram Paul Prabhakar Abhilash (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: Emergency department (ED) revisits are an important measure of health-care quality provided by any medical center. This study analyzes the profile and outcome of patients revisiting the ED within 72 h at a tertiary care center in South India. Methods: This was a retrospective cohort study done on all patients presenting to ED within 72 h of their first visit over 5 months. Unavoidable revisits and the factors associated with them were categorized, coded, and analyzed. Results: The ED revisit rate was 2.9% (900/30409). Based on standard triaging criteria, patients during their first visit were triaged as follows: 8.2% as priority 1, 32% as priority 2, and 58.2% as priority 3. During the revisit, they were triaged as follows: 12.9% (+3.7% increase) as priority 1, 36.9% (+4.9% increase) as priority 2 and 49.1% (-9.1% decrease) as priority 3. Approximately a quarter (27%) of the patients had to be prioritized higher on their revisit. Abdominal pain (18.3%), vomiting/diarrhea (11.7%), bleeding from the previous wound site (10.5%), and fever (9%) were the most common presenting complaints. Avoidable revisits included 13.4% (n = 121) patients. Multivariate logistic regression analysis showed age >40 years (adjusted odds ratio [OR]: 1.60; 95% confidence interval [CI]: 1.04–2.46; P: 0.031) and abdominal pain (adjusted OR: 2.07;95% CI: 1.40–3.08; P: <0.001) to be independent predictors of unavoidable ED revisits. In addition, age >40 years (adjusted OR: 3.53; 95% CI: 2.12–5.88; P: <0.001) and fever (adjusted OR: 0.57;95% CI: 0.37–0.90; P: 0.015) were found to be independent risk factors for patients revisiting as priority 1 versus other priorities. Among the revisiting patients, 15.4% required admission. Conclusion: Gastrointestinal symptoms and fever were found to be the most common symptoms that warranted a revisit. Abdominal pain and age >40 years were found to be associated with higher odds of an unavoidable revisit. In addition, age >40 years and fever were associated with sicker patients on revisits.